Unified D-α-Tocopherol 5-Fu/SAHA bioconjugates self-assemble as complex nanodrug for optimized combination therapy. (27th June 2018) - Han, Leiqiang; Wang, Tianqi; Mu, Shengjun; Yin, Xiaolan; Liang, Shuang; Fang, Hao; Liu, Yongjun; Zhang, Na
Aim: To optimize the synergistic efficacy of combination therapy with controlled molar ratio, complex small molecule-based nanodrug (Co-SMND) of 5-fluorouracil (5-Fu)/vorinostat (SAHA) was developed.Materials & methods: Co-SMND with various ratios of 5-Fu-D-α-tocopherol (VE)/SAHA-VE were prepared and characterized including co-assembly mechanism, hydrolytic stability, cytotoxicity, synergistic effect and apoptosis inducing ability. The antitumor activity, systematic toxicity and biodistribution of optimized Co-SMND were evaluated in CT-26 bearing BALB/c mouse.Results: Maximal synergistic effect of Co-SMND could be obtained via simply adjusting the feeding molar ratio. The optimized Co-SMND showed superior in vivo antitumor efficacy, upregulated security and selective intratumoral accumulation.Conclusion: Such Co-SMND is of great significance for future clinical translation, and would be an efficient platform for combination chemotherapy.